Sorafenib, a dual Raf kinase/vascular endothelial growth factor receptor inhibitor has significant anti-myeloma activity and synergizes with common anti-myeloma drugs - Ramakrishnan, V (2009)
Multiple myeloma is characterized by increased bone marrow neovascularization driven in part by vascular endothelial growth factor (VEGF). In addition, the Ras/Raf/MEK/ERK pathway is critical for the proliferation of myeloma cells and is often upregulated. Sorafenib (Nexavar) is a novel multi-kinase inhibitor that acts predominantly through inhibition of Raf-kinase and VEGF receptor 2, offering the potential for targeting two important aspects of disease biology. In in vitro studies, sorafenib-induced cytotoxicity in MM cell lines as well as freshly isolated patient myeloma cells. It retained its activity against MM cells in co-culture with stromal cells or with interleukin-6, VEGF or IGF; conditions mimicking tumor microenvironment. Examination of cellular signaling pathways showed downregulation of Mcl1 as well as decreased phosphorylation of the STAT3 and MEK/ERK, as potential mechanisms of its anti-tumor effect. Sorafenib induces reciprocal upregulation of Akt phosphorylation; and simultaneous inhibition of downstream mTOR with rapamycin leads to synergistic effects. Sorafenib also synergizes with drugs such as proteasome inhibitors and steroids. In a human in vitro angiogenesis assay, sorafenib showed potent anti-angiogenic activity. Sorafenib, through multiple mechanisms exerts potent anti-myeloma activity and these results favor further clinical evaluation and development of novel sorafenib combinations.